Wortmannine F and G, two new pyranones from Talaromyces wortmannii LGT-4, the endophytic fungus of Tripterygium wilfordii. (February 2019) - Zhao, Jun-Wen; Yang, Zhong-Duo; Zhou, Shuan-Yan; Yang, Li-Jun; Sun, Jian-Hui; Yao, Xiao-Jun; Shu, Zong-Mei; Li, Shuo
Graphical abstract: Highlights: Two new pyranones were isolated from Talaromyces wortmannii . Structures were established by means of spectroscopic methods. Compounds1 and2 exhibited potent PI3Kα inhibitory activity. Abstract: Two new pyranones, Wortmannine F (1 ) and G (2 ), were isolated from Talaromyces wortmannii LGT-4, which is an endophytic fungus from Tripterygium Wilfordii . Their structures were elucidated on the basis of NMR and ESI-MS spectral data, as well as chemical calculation. Additional known compounds (4 –8 ) were also isolated. The isolates were tested for monoamine oxidase (MAO), acetylcholinesterase (AChE) and phosphoinositide 3-kinase α (PI3Kα) inhibitory activities. Compounds1, 2 showed potent PI3Kα inhibitory activity with IC50 of 25 and 5 μM, respectively.